Влияние близких отношений на развитие ребенка - Убайдуллаева Дилёрабону Санжаровна (Academia One, 2024)
communication is as necessary for a child as food. A baby who receives adequate nutrition and good medical care, but is deprived of constant contact with family, develops poorly not only mentally, but also physically: he does not grow, loses weight, and loses interest in life. “Problem”, “difficult”, “disobedient” and “impossible” children, just like children “with complexes”, “downtrodden” or “unhappy” are always the result of incorrect relationships in the family
Keywords: children; emotional support; communication